Surveying the employed Nurses' Organizational Commitment in Selected Tehran University of Medical Sciences Hospitals - F Akbari Haghighi; Z Koohi Rostamkalaee; A Pourreza; A Rahimi Forshani (Tehran University of Medical Sciences, 2014)
Abstract Background: Organizational commitment is an important occupational attitude which demonstrates personnel staffs liability for their organization. This study aimed at assessing the level of nurses' organizational commitment in selected hospitals of Tehran University of Medical Sciences in 2011. Materials and Methods: In this cross - sectional study, 363 nurses with BS and MS degree who employed in selected hospitals of TUMS were chosen using random sampling method. Data were collected using a 2-section questionnaire including demographic variables and organizational commitment. With the intention of data analysis, descriptive statistics, independent t -test, chi square, Kruskal-Wallis, Mann-Whitney tests were conducted. Significant level assumed at 0.05. Results: Study results confirmed that organizational commitment and its all dimensions (affective, continuous and normative) were in moderate level (65.87± 15.32). The Level of organizational commitment had significant relation to job position (P<0.001), ward type (P0.05). Conclusion: Since, None of the demographic variables revealed significant association with organizational commitment and occupational and organizational factors had significant relation with organizational commitment, it seems that personal factors should not be considered as the main criteria of recruiting committed nurses